Role of Knowledge Economy and Innovations in Entrepreneurship; Case study in Sri Lanka - Fernando, N.V.; Perera, G.A.N.; Amaratunge, S.P.P. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This study aims to explore how knowledge economy and innovations contribute to the success of entrepreneurship and thereby to the development of the economy by comparing Sri Lanka with few selected emerging economies who have succeeded in this context. Exploring Sri Lankan situation with few other selected countries would serve the purpose to understand the standpoint of the country within the context. A country comparison between, Sri Lanka, Singapore, Thailand, Malaysia, South Korea, Japan, China, and India was conducted. The findings showed that Sri Lanka has many more to learn from the success stories of these emerging economies and should pave the way to the development by boosting the entrepreneurship and stressing the importance of innovation and knowledge economy in the country. Suggestions to overcome the gap mentioned above was provided and that is expected to provide a catalyst to the Sri Lankan entrepreneurs, innovators and small and medium enterprises in being internationally competitive.
Keywords: Knowledge Economy, Innovations, Entrepreneurship, Sri Lanka